CONCENTRATION OF CINNAMON ON QUALITY OF CANDIED PINEAPPLE PITH (Ananas comosus L. Merr) DURING STORAGE - Marwita Marwita; Raswen Efendi; Evy Rossi (Universitas Riau, 2021)
The purpose of this research is to obtain the best concentration of cinnamon on the quality of candied pineapple pith (Ananas comosusL. Merr) during storage. This research used a Completely Randomized Design (CRD) with five theatments and three replications to obtain 15 experimental units. The treatments in this study were K1 (6% cinnamon concentration), K2 (8% cinnamon concentration), K3 (10% cinnamon concentration), K4 (12% cinnamon concentration), and K5 (14% cinnamon concentration). The data obtained were analyzed statistically using ANOVA and DNMRT test at 5% level. The results showed that the concentration of cinnamon in candied pineapple pith significantly affected the water content, total sugar content, pH, vitamin C, total plate count, overall descriptive and hedonic sensory assessment. The best treatment after 18 days of storage was K3 treatment (10% cinnamon concentration) with an average moisture content of 24.46%, total sugar content of 19.90%, acidity (pH) 4.36, vitamin C 1.08 mg/100 g, and total plate counts of 71,00 × 10^3 koloni/g. Overall sensory assessment favored by panelists with a description of yellowish brown color, very aromatic pineapple and cinnamon, taste of cinnamon and slightly hard texture. Keywords: Candied,Cinnamon, Pineapple